Nutrient Management Recommendations Based on Mehlich-3 Extractant for Calcareous Soils in Miami-Dade County - Yuncong Li; Qiang Zhu; Rao Mylavarapu; Kelly Morgan; Guodong Liu; Jonathan Crane; Qingren Wang; Henry Mayer; Jeff Wasielewski; Laura Vasquez; Qingchun Liu; Teresa Olczyk (EDIS)
This factsheet provides information about the history of soil testing calibrations and justification for recommending extraction of soil nutrients using Mehlich-3 for calcareous soils in Miami-Dade County. The dominant soils from this County have an extraordinarily high concentration of calcium resulting in high pH. This document also includes UF/IFAS approved Mehlich-3 extractant-based testing interpretations and recommendations for these soils. The purpose of this publication is to elucidate an appropriate approach for analyzing the unique calcareous soils from Miami-Dade County for plant available nutrients. The target audiences are Extension agents, agronomists at soil testing laboratories, crop advisors, growers, representatives of the state and local agencies, and others concerned about soil testing and plant analysis in Miami-Dade County.